A study of mishandling mail in MASkargo / Mohammad Hafiz Ramli - Ramli, Mohammad Hafiz (Faculty of Business and Management, 2010)
This case study will focus on the mail handling in MASkargo. Mishandling as define by Maan (1993) comprise of delayed or lost bag. Meanwhile Ericsson (1997) delivery accuracy is one of the biggest problems in Swedish industry. The definition of delivery accuracy is how good the shipment can be delivered in promised time, (Mattson 1999).This study is focusing on how the mishandle is happen based on the obeservation made during the process handling, and also determine the factor that lead to the mishandling mail in MASkargo. More over in this study there is a gap analysis between the actual practice that is state in the manual with the current practice that is done in MASkargo. Lastly in this study, it contain a conclusion and also some recommendation for MASkargo.